Proactive psychosomatic approach to the post-COVID depression treatment - Khaustova, Olena; Assonov Дмитро Олексійович; Asanova Азізе Ельдарівна (Psychosomatic Medicine and General Practice, 2021)
Background. Recently a proactive model of psychosomatic medicine has been widely implemented in the world, namely a new way of providing psychiatric services in general medical departments, based on the principles of initiative, focus, intensity, and integration with general care. Postcovid depression is a major challenge for the mental health system, so the introduction of such a proactive model to provide specialized care to patients with depressive disorders within the ward of multidisciplinary hospitals is promising. During the COVID-19 pandemic, the proportion of depressed patients in somatic hospitals tripled compared to the previous period. Early diagnosis and treatment of postcovid mental disorders, including depression, already in inpatient COVID-19 therapy period should increase the effectiveness of therapy and improve the quality of life of patients. Research is needed to study how the proactive psychosomatic medicine model implementation can reduce the negative burden of postcovid mental problems, including depressive disorders. Objective. The study was to evaluate the effectiveness of proactive psychosomatic intervention in the form of 8-week escitalopram monotherapy in patients with postcovid depression. Materials and methods. The proactive psychosomatic intervention consisted of early diagnosis and subsequent treatment (first inpatient, then outpatient) of depressive disorders in 44 patients with COVID-19. After obtaining informed consent, the Hospital Anxiety and Depression Scale (Depression Subscale, HADS-D≥11) was used to screen for depression. The Hamilton Depression Scale (HAM-D), the Somatic Symptom Scale (SSS-8), and Chaban’s Quality of Life Scale (CQLS) were used to assess symptoms and dynamics. The pharmacological intervention consisted of escitalopram (Medoprami, Medochemi Ltd) 10 mg per day for mild to moderate depression, and 20 mg per day with severe depression. Results. According to the proactive model of counseling-liaison psychiatry, patients who were hospitalized with COVID-19were screened for signs of active mental health problems, namely depression. 65.7% of them had clinically significant depression (≥11 on Depression Subscale of Hospital Anxiety and Depression Scale) and they were to be treated with pharmacotherapy. Significant reductions in mental and somatic symptoms of depression and improved quality of life were observed in patients with postcovid depression after an 8-week course of escitalopram therapy. At the beginning of the study, 12 (28.58%) people had a mild degree of depression, 15 (35.71%) - moderate, and 15 (35.71%) - severe. At the end of the 8th week of taking the drug, 24 (57.14%) people had no signs of depression on the HAM-D scale, 18 people had subclinical depressive features. There were improvements in quality of life and the reduction of somatic symptoms. Changes in the mean scores were: on HADS scale  = -7.90, on HAM-D scale  = -14.21, on SSS-8 scale  = -2.38, on CQLS scale  = + 11.31 points. Conclusions. Proactive psychosomatic medicine model implementation in the multidisciplinary hospital for patients with depressive disorders was timely and appropriate because it provided early screening for depression and early escitalopram treatment for postcovid depression. Escitalopram (Medopram, Medochemi Ltd) may be a promising drug for the psychopharmacotherapy of depressive symptoms in patients with COVID-19. Further study of its effectiveness in the treatment of postcovid depression is needed.